Medicalização dos adolescentes em conflito com a lei - Santos, Anna Tereza de Oliveira (2018)
The medicalization process has been growing over the years in modern society. In general, the concept of medicalization has been used in several studies to deal with a phenomenon that has traditionally had the general sense of reducing social and political problems in private and individual problems. This present aims to analyze the contemporary expressions of medicalization in adolescents in conflict with the law. Taking as a starting point the studies on the biopolitics of the population of Michel Foucault and the reflections of authors like Cristian Dunker and Vladmir Safatle on the expansion of diagnostic categories, these work seeks to understand how the medical and psychiatric discourses are being used by legal knowledge as instrument of normalization, arbitrary social control and management of adolescents who commit an infraction.